Contrast-enhanced Ultrasound (CEUS) vs contrast-enhanced computed tomography for multilocular cystic renal neoplasm of low malignant potential: A retrospective analysis for diagnostic performance study. Issue 46 (13th November 2020) - Shan, Kun; FU, A BU DU LI AI ZE ZI HA LI; Liu, Ningning; Cai, Qiliang; Fu, Qingfeng; Liu, Leyi; Sun, Xiaoyu; Zhang, Zhihong
Abstract : Abstract: Multilocular cystic renal neoplasm of low malignant potential (MCRNLMP) might be benefited from nephron-sparing surgery. Contrast-enhanced computed tomography is used for the diagnosis of MCRNLMP but contrast-enhanced ultrasound has lack of nephrotoxicity and several advantages over contrast-enhanced computed tomography and contrast-enhanced magnetic resonance. The purpose of the study was to compare diagnostic parameters of preoperative contrast-enhanced ultrasound against contrast-enhanced computed tomography for the detection of MCRNLMP in patients who faced curative surgery for complex cystic renal mass. Data regarding contrast-enhanced ultrasound, contrast-enhanced computed tomography, and clinicopathological results of 219 patients who underwent curative surgery for complex cystic renal mass (Bosniak classification III or IV) were retrospectively collected and analyzed. Bosniak classification for imaging modality and the 2016 WHO criteria for clinic pathology were used for detection of MCRNLMP. Contrast-enhanced ultrasound, contrast-enhanced computed tomography, and clinicopathology were detected 68, 66, and 67 as a MCRNLMP respectively. Contrast-enhanced ultrasound and contrast-enhanced computed tomography had 30.37% and 29.27% sensitivities for the detection of MCRNLMP. While 60% and 50% specificities respectively. Bosniak classification III ( P = .045) and lower mean Hounsfield unit ( P = .049) were associated with the prevalence of MCRNLMP. Contrast-enhanced computed tomography was detected 6 and 7, while contrast-enhanced ultrasound detected 3 and 2 complex cystic renal mass as false positive and false negative MCRNLMP respectively. A contrast-enhanced ultrasound had 0.011 to 1.0 diagnostic confidence and contrast-enhanced computed tomography had 0.045 to 0.983 diagnostic confidence for decision making of nephron-sparing surgeries. Contrast-enhanced ultrasound may have better visualization of MCRNLMP than contrast-enhanced computed tomography. Level of Evidence: III.